2020
DOI: 10.1186/s13068-020-01828-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of fermentation inhibitors from pre-hydrolysis liquor using polystyrene divinylbenzene resin

Abstract: Background The presence of soluble lignin, furfural and hydroxymethylfurfural (HMF) in industrial pre-hydrolysis liquor (PHL) from the pulping process can inhibit its bioconversion into bioethanol and other biochemicals. Although various technologies have been developed to remove these inhibitors, certain amounts of sugars are also inevitably removed during the treatment process. Hence, polystyrene divinylbenzene (PS-DVB) resin was used as an adsorptive material to simultaneously remove ferment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 53 publications
(83 reference statements)
0
15
1
Order By: Relevance
“…Individual 0.2 mL aliquots were taken at 2 h, 4 h, 6 h, 12 h, 24 h, 48 h, and 72 h. Each sample was frozen and preserved until further analysis. The collected samples were centrifuged at 10,000 rpm for 5 min to obtain a supernatant which was analyzed for sugars by HPLC (Agilent 1260 Series) [ 47 ]. Enzymatic hydrolysis efficiency of the AWWS was calculated according to the following equation: where 0.9 is the factor that converts glucose to equivalent glucan.…”
Section: Methodsmentioning
confidence: 99%
“…Individual 0.2 mL aliquots were taken at 2 h, 4 h, 6 h, 12 h, 24 h, 48 h, and 72 h. Each sample was frozen and preserved until further analysis. The collected samples were centrifuged at 10,000 rpm for 5 min to obtain a supernatant which was analyzed for sugars by HPLC (Agilent 1260 Series) [ 47 ]. Enzymatic hydrolysis efficiency of the AWWS was calculated according to the following equation: where 0.9 is the factor that converts glucose to equivalent glucan.…”
Section: Methodsmentioning
confidence: 99%
“…Acetic acid had the highest concentration, whereas 5-HMF had the lowest concentration among the degradation products. Notably, short time extraction showed a much lower concentration of degradation products than conventional hot water extraction, which lasted over 1 h. Thus, short-time extracts have lower biotoxicity, as these degradation products inhibit the biological fermentation of sugars into biofuels (Huang et al 2020). The acetic acid concentration in conventional hot water extraction was reported to reach 1.6 to 4.1 g/L, which was much higher than the acetic acid concentrations in the extracts of the short-time treatments listed in Table 1.…”
Section: Sugars and Lignins In Hydrolysate Of Poplar Woodmentioning
confidence: 99%
“…Recent studies suggested that converting the cellulose and hemicellulose of biomass to monomeric sugars and biofuels could be a great road to meeting the urgent need for renewable alternative carbon resources (Robertson et al, 2017;Huang et al, 2019;Lin et al, 2019). Among the agricultural wastes, corncob has been widely concerned for its richness in hemicellulose, which is often used to produce xylose, xylitol, xylo-oligosaccharides, or furfural (Si et al, 2009b(Si et al, , 2013bZhang et al, 2014;Hu et al, 2016;Liu et al, 2016;Huang et al, 2020b). However, a large amount of corncob residue is produced and it is usually used for burning to generate heat or electricity, cultivation, feed, or just discarded.…”
Section: Introductionmentioning
confidence: 99%